2021
DOI: 10.3389/fmolb.2021.665492
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Redox Homeostasis in Protein Quality Control

Abstract: Bacteria live in different environments and are subject to a wide variety of fluctuating conditions. During evolution, they acquired sophisticated systems dedicated to maintaining protein structure and function, especially during oxidative stress. Under such conditions, methionine residues are converted into methionine sulfoxide (Met-O) which can alter protein function. In this review, we focus on the role in protein quality control of methionine sulfoxide reductases (Msr) which repair oxidatively protein-boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Despite the progress in deciphering possible interactions between Met sulfoxidation and protein carbonylation or protein phosphorylation [27,[95][96][97], the molecular mechanisms coupling oxidative signals to changes in phosphorylation in seeds still remain poorly understood. Interestingly, two of identified proteins containing oxidized Met and a phosphorylation site corresponded to an elongation factor and an inhibitor of serine proteases (Table 2), and were previously demonstrated to be substrates for MSRB1 [23] and periplasmic MSR [98], respectively. Hence, 2Dd-CNBr-based results might provide initial information toward a better understanding of the interplay between different types of post-translational protein modifications in targeted proteins.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the progress in deciphering possible interactions between Met sulfoxidation and protein carbonylation or protein phosphorylation [27,[95][96][97], the molecular mechanisms coupling oxidative signals to changes in phosphorylation in seeds still remain poorly understood. Interestingly, two of identified proteins containing oxidized Met and a phosphorylation site corresponded to an elongation factor and an inhibitor of serine proteases (Table 2), and were previously demonstrated to be substrates for MSRB1 [23] and periplasmic MSR [98], respectively. Hence, 2Dd-CNBr-based results might provide initial information toward a better understanding of the interplay between different types of post-translational protein modifications in targeted proteins.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the PPO gene downregulation was observed for the melatonin-treated litchi samples. On the contrary, several studies have shown that the Msr-related genes regulated oxidative stress by mediating sulfoxylation of methionine, participated in the redox regulation in the organisms ( Jiang et al, 2017 , 2018 ; Moskovitz and Smith, 2021 ), and also repaired oxidatively damaged protein ( Aussel and Ezraty, 2021 ; Xiao et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role of methionine sulfoxide reductases in protecting living cells from oxidative stress has long been recognized; however, the role of these enzymes in enhancing the survival of bacterial pathogens in the host is still not fully understood [ 1 , 2 , 3 , 4 ]. Bacterial pathogens inhabit an environment that promotes oxidative stress, in which enzymes of the host innate immune response such as NADPH oxidase, superoxide dismutase and myeloperoxidase produce superoxide radicals, hydrogen peroxide and hypochlorite, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of methionine residues can lead to a loss of biological function by disrupting protein structure, and methionine sulfoxide reductases are required to reverse oxidative damage to free and protein-bound methionine residues [ 1 , 2 ]. The cytoplasmic peptide-methionine sulfoxide reductases MsrA and MsrB that use a thiol-based redox relay for catalysis and reduce the S- and R- stereoisomers of methionine sulfoxide (MetSO), respectively, are particularly well studied [ 2 , 3 , 6 ]. However, periplasmic or outer-membrane-associated methionine sulfoxide reductases have recently been shown to play a pivotal role in protecting various bacterial pathogens from exogenous oxidative stress.…”
Section: Introductionmentioning
confidence: 99%